2016
DOI: 10.1016/j.virol.2016.05.021
|View full text |Cite
|
Sign up to set email alerts
|

Domain I of the 5′ non-translated genomic region in coxsackievirus B3 RNA is not required for productive replication

Abstract: Domain I is a cloverleaf-like secondary structure at the 5' termini of all enterovirus genomes, comprising part of a cis-acting replication element essential for efficient enteroviral replication. 5' genomic terminal deletions up to as much as 55% of domain I can occur without lethality following coxsackie B virus infections. We report here that the entire CVB structural domain I can be deleted without lethality.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 21 publications
0
8
0
Order By: Relevance
“…On the other hand, it is not always correct to consider the mutational loss of the capacity to trigger an obvious cytopathic effect (CPE) (e.g., a lack of plaque-forming activity) sufficient evidence for killing of the virus, as usually done. For example, as already mentioned, complete destruction of the CVB3 replicative element oriL (99) or cre (149), resulting in a loss of cytopathic activity, is nevertheless compatible with viral viability: such viruses are able to grow, though with a greatly diminished efficiency, causing persistent, noncytopathic infections. An FMDV variant that accumulated various debilitating mutations during multiple plaque-to-plaque (bottlenecking) passages represented another example of conversion of a lytic virus into a noncytocidal one (290).…”
Section: (Relative) Neutrality Of Various Mutationsmentioning
confidence: 93%
See 1 more Smart Citation
“…On the other hand, it is not always correct to consider the mutational loss of the capacity to trigger an obvious cytopathic effect (CPE) (e.g., a lack of plaque-forming activity) sufficient evidence for killing of the virus, as usually done. For example, as already mentioned, complete destruction of the CVB3 replicative element oriL (99) or cre (149), resulting in a loss of cytopathic activity, is nevertheless compatible with viral viability: such viruses are able to grow, though with a greatly diminished efficiency, causing persistent, noncytopathic infections. An FMDV variant that accumulated various debilitating mutations during multiple plaque-to-plaque (bottlenecking) passages represented another example of conversion of a lytic virus into a noncytocidal one (290).…”
Section: (Relative) Neutrality Of Various Mutationsmentioning
confidence: 93%
“…The interaction between these ligands is important for the initiation of the synthesis of both the viral (positive) and complementary (negative) RNA strands (89,93,(95)(96)(97)(98). It was recently shown that (at least in the case of coxsackievirus B3 [CVB3]) oriL, which is required for efficient genome replication, is not indispensable for viral viability: its removal does not kill the virus but rather decreases the efficiency of its RNA replication ϳ10 5 -fold (99). It should be noticed, however, that the nonessentiality of oriL has so far been shown only for this particular virus (see also a reservation at the end of this section).…”
Section: Introductionmentioning
confidence: 99%
“…Natural deletions within the 5′NCR of EV-B RNA populations can affect functional secondary-structural elements of the RNA domain I (cloverleaf, CL) 9 – 11 altering formation or stability of viral replication complexes and consequently decreasing genomic replicative capacities of 5′TD viral RNA forms 12 14 . Moreover, it was evidenced that the 5′triphosphorylated cloverleaf structure of CVB3 RNA is sufficient to induce a type 1 IFN response by the RIG-I signalling pathway 10 .…”
Section: Introductionmentioning
confidence: 99%
“…Nonetheless, accumulation of longer 5′ terminal deletions appears to have limits, as passage of the CVB3-TD virus with a terminal 49-nucleotide deletion (CVB3-TD50) in primary cell cultures and in mice failed to create a population of TDs with deletions greater than 49 nucleotides [ 50 , 61 ]. Despite our observation that naturally occurring 5′ TD deletions larger than 49 nucleotides do not occur (or, more likely, are exceedingly rare), we created a CVB3-TD genome deleted through stem-loop d (CVB3-TD78) that retained the ability to replicate in HeLa cells and generate the virus, albeit with a 100,000-fold reduction in virus particle production [ 69 ]. We suggest that the lack of observed stable populations of TD CVB genomes with deletions greater than 49 nucleotides from the 5′ end is more likely to be the result of reduced fitness within the maelstrom of constantly occurring TD RNAs in an infected cell, rather than TDs without stem-loop d ever occurring.…”
Section: Discovery and Characterization Of A Novel Late-stage “Noninf...mentioning
confidence: 99%